A robust framework for cloud‐based software development outsourcing factors using analytical hierarchy process. Issue 2 (1st July 2020) - Akbar, Muhammad Azeem; Khan, Arif Ali; Mahmood, Sajjad; Alsanad, Ahmed; Gumaei, Abdu
Abstract: Managing the cloud‐based software development outsourcing (CSDO) activities across the geographically distributed development sites are much challenging. This study aims to identify the success factors (SFs) for CSDO and prioritize them based on their significance. To achieve this objective, we conducted a systematic literature review (SLR) and survey study with industrial and academic experts. Finally, we applied the analytical hierarchy process (AHP) to develop the framework based on the prioritization of the identified SFs. We believe that the findings of this study will assist the industry practitioners and researchers in developing effective strategies for the successful implementation of CSDO activities. Abstract : The aim of this framework is to assist the industry practitioners and researchers in developing effective strategies for cloud‐based software development outsourcing activities. It provide a roadmap to consider the most critical factors before scaling the software development outsourcing activities on cloud platform.